Geospatial technologies in post-war reconstruction: challenges and innovations in Ukraine - Nazarenko, V.; Martyn, A. (Land Management, Cadastre and Land Monitoring, 2024)
Ukraine's post-war reconstruction requires effective strategies to transform war-torn areas into resilient, smart cities, with geospatial technologies playing a pivotal role. Several key scientific methods had been employed for the study, including data extraction and analyses, system modeling and complexity decomposition. This study explores the challenges and innovations in applying geospatial technologies to Ukraine's reconstruction efforts. It examines data accuracy and availability, the integration of ecological and urban planning within GIS frameworks. Key challenges identified include data inaccuracy, technological limitations, and a shortage of skilled professionals. Innovations such as the development of the GIS for Regional Development and integration with the Digital Restoration Ecosystem for Accountable Management (DREAM) aim to address these issues. A sustainable economic reconstruction model is presented, emphasizing geospatial data integration. Enhancing legislation on geospatial data infrastructure and implementing capacity-building initiatives are essential. Effective integration of advanced geospatial technologies and improved legislation will enable Ukraine to meet reconstruction demands, fostering sustainable urban environments and serving as a model for other nations.Keywords: urban renovation, GIS, restoration economy, sustainable development, innovation technology, urban economics.
Keywords: urban renovation; GIS; restoration economy; sustainable development; innovation technology; urban economics